Penguatan Sumber Daya Manusia Melalui Reformasi Lembaga Pendidikan dan Tenaga Kependidikan di Sumatera Barat (STAI Terpadu Yogyakarta, 2022)
The purpose of this research is that education is a big responsibility of a nation. All components and factors supporting the success of education have a very close relationship. Educational staff include school/madrasah principals, education unit supervisors, administrative staff, librarians, laboratory personnel, technicians, study group managers, tutors and cleaners. In the context of educational institutions, one of the key factors for the success of managing educational institutions is the leadership of school/madrasah principals, pesantren caregivers, deans, rectors, and all elements of education. This research is a conceptual research using qualitative methods. The results of the study indicate that human resources are company assets that must be maintained. Empowerment of human resources that is managed regularly and systematically will produce quality and competitive human resources.